Odefinierade platser i staden : med studie i Söderälje - Berggren, Caroline (SLU/Dept. of Urban and Rural Development, 2008)
The purpose of this master thesis is to attract attention to the undefined spaces of our urban landscape and emphasize the need of these spaces in the city. The different values of these spaces are here clearly presented so that they can be considered when real estate developers show a particular interest in any one of these undefined spaces.